El juego físico en el desarrollo motriz grueso de los niños de nivel inicial II, en el centro de educación inicial Eloy Alfaro, de la ciudad de Riobamba, periodo 2020-2021 - Parra Rodríguez, Gilda Carolina (2021)
This research covers important contents referring to the pre-school stage of the child, which are physical play in the gross motor area, presented with the title “Physical play in the gross motor development of second-level children, in the Eloy Alfaro elementary education center, from the city of Riobamba, during 2020-2021”. This inquiry aimed to justify those physical games and their classification, which involves psychomotor, recreational, locomotor, athletic, free, collective, organized, strength and speed games, as well as gross motor skills and their topics such as coordination, balance, laterality, tonicity, body scheme, reflexes, and stages, are of utmost importance when applied to the students of initial 2. The methodology used in the research is descriptive, which consists of collecting different data and information that allows analyzing and describing the objectives that the investigation requires. The population used in the study were 4 teachers and 30 children of the initial area 2, where a survey was used for teachers and a checklist for students. In conclusion, the classification of physical games is directly complemented by the child's gross motor skills, suggesting that the theoretical and the practical work together. Therefore, using the theory of gross motor skills focused on a practice will give better results. Keywords: Psychomotor, gross motor skills, game, physical game, initial level.